1999
DOI: 10.1002/(sici)1097-4636(1999)48:4<458::aid-jbm9>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Potential thermal artifacts in hip joint wear simulators

Abstract: Frictional heat was monitored during wear tests of ultrahigh molecular weight polyethylene acetabular cups bearing against femoral balls of metal or ceramic in a hip simulator, using bovine serum as a lubricant. About 1 to 2 h of continuous cycling were required for the temperature in the zone of contact between the cup and ball to rise to its maximum steady value, and this equilibrium temperature was markedly higher with increased load and/or cycling rate. Frictional heating caused substantial precipitation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…However, in this simulator study these types of third bodies were not present. Some studies reported the formation of calcium-phosphate layers on the articulating metallic surfaces [24], which may possibly chip off during articulation and cause third body wear.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this simulator study these types of third bodies were not present. Some studies reported the formation of calcium-phosphate layers on the articulating metallic surfaces [24], which may possibly chip off during articulation and cause third body wear.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the result of thermal heating at the articulating surfaces when testing at 2 Hz. PEEK is considered a thermal insulator (thermal conductivity of 0.25 W/mK) as compared to the more common material of CoCr (thermal conductivity of 18 W/mK), and this may have resulted in denaturization of the proteinaceous lubricant, potentially forming a protective triobolayer [27][28][29]. This is supported by the results for Group 3, where a reduced protein content of 5 g/L and a decrease in the lubricant temperature to 23掳C was performed to reduce any thermal artifact and further minimize protein denaturization.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13]29,30 The articulating surfaces were subjected to a biaxial rocking motion with a peak load of 2.1 kN applied at 1.13 Hz. Further details of the simulator conditions have been provided in earlier publications.…”
Section: Hip Simulatormentioning
confidence: 99%